Avaliação epidemiológica, clínica e microbiológica das infecções da corrente sangüínea por Candida spp. na população idosa - Guimarães, Thaís [UNIFESP] (2008)
Hematogenous candidiasis is a serious infection that is highly prevalent in medical centers worldwide. In order to better understand the epidemiology and optimize strategies to control bloodstream infections caused by Candida spp., this infection has been studied in specific populations, such as patients at intensive care units, hematologic and neonates. Few information is available about the epidemiology of these infections in elderly patients. Due to the increase of human life expectancy, high incidence of candidemia in elderly patients and the limited number of studies available in the literature, this study aimed to analyze the epidemiological, clinical and microbiological features in elderly patients, compared to young adult population, in terms of Candida species distribution, resistance to antifungal agents, mortality rate and prognostic factors. We analyzed a database included data from three cohort cross-sectional studies collected prospectively in order to determine the epidemiological, clinical and microbiological characteristics of episodes of candidemia documented in 14 hospitals during the period of June 1994 to December 2004. The clinical and epidemiological information were obtained by reviewing medical records and were recorded in standard case report form. Candidemia was defined as at least one positive blood culture for Candida spp., after proper antisepsis, being only the first episode of candidemia considered for characterization of clinical cases. Individuals were categorized as young adults when aged between 14 and 59 years and older persons when aged ≥ 60 years. All pediatric patients (age <14 years) were excluded from the analysis. The characterization of microbial strains was performed in a single laboratory (LEMI-UNIFESP) by conventional methods. Antifungal susceptibility tests were performed using the broth micro dilution assay according to the methodology by the Clinical and Laboratory Standards Institute (CLSI). All data were stored in database and statistical analysis was performed by SPSS version 15.0 and EPI-INFO version 6.0. We analyzed a total of 1.037 cases and the prevalence of elderly in the population studied was 45.2% (469/1037) and 59.3% were male. The candidemia in the elderly occurs more frequently in severe patients, hospitalized at intensive care units, in patients with cancer, diabetes mellitus, cardiac and lung diseases and in patients submitted to central venous catheterization and abdominal surgeries. C. albicans was responsible for most cases of candidemia in the elderly and C. tropicalis was the non-albicans species significantly more prevalent in this age group. There was no difference between the distribution of azole resistance in the age groups evaluated and this occurrence demonstrated to remain stable along the study period. However, cross-resistance was observed. The mortality rate of elderly population was greater than that observed with young adults (69.7% vs. 44.5%, p <0.001) regardless of initial antifungal therapy and the isolated species. The prognostic factors independently associated with death in the elderly population were APACHE II score > 20, presence of heart disease, pulmonary disease, dialysis, abdominal surgery and use of corticosteroids. Elderly patients account for substantial casuistic of candidemia in tertiary hospitals, presenting peculiar features of natural history and high mortality rate. Therefore, is essential to consider more aggressive approach in prophylaxis and antifungal therapy for this population.